Carborane-linked 2′-deoxyuridine 5′-O-triphosphate as building block for polymerase synthesis of carborane-modified DNA. Issue 21 (1st November 2017) - Balintová, Jana; Simonova, Anna; Białek-Pietras, Magdalena; Olejniczak, Agnieszka; Lesnikowski, Zbigniew J.; Hocek, Michal
Graphical abstract: p -Carborane-linked dUTP was synthesized and used as a substrate in polymerase catalyzed enzymatic synthesis of carborane-modified DNA (with up to 21 carborane units). Abstract: 5-[( p -Carborane-2-yl)ethynyl]-2′-deoxyuridine 5′- O -triphosphate was synthesized and used as a good substrate in enzymatic construction of carborane-modified DNA or oligonucleotides containing up to 21 carborane moieties in primer extension reactions by DNA polymerases.